RISK COMMUNICATION STRATEGY IN DEALING WITH THE TSUNAMI DISASTER - Marlinda Irwanti; Dian Nuriman; Puji Lestari; Ridzki Sigit (Lafadz Jaya Publisher, 2023)
Umang Beach Club Private Island Resort is located in Sumur village, Pandeglang, Banten. Has a unique location, located at two potential tsunami sources. The first is Seismic, which is at the center of the Sunda Strait megathrust. The second, namely Unsesmic, is located at a distance of about 70km from Mount Anak Krakatu. This study aims to find a risk communication strategy in dealing with the tsunami natural disaster. This study used a qualitative descriptive method and collected data by interviews, documentation and observation. Interviews were conducted with informants, namely local governments and disaster-related institutions. The results of the study found that risk communication strategies in dealing with tsunamis were initiated by common perceptions of the tsunami hazard, setting goals, developing messages, face-to-face communication.